Assessment of the Effect of Temperature and Annealing Time on Homogenization of AlCu4MgMn Alloys - Weiss, V. (Металлофизика и новейшие технологии, 2013)
Homogenization is defined as a method of heat treatment, which consists of holding time at high temperature near the liquidus (approx. 0.7 to 0.8 of the melting temperature) to eliminate chemical inhomogeneity diffusion processes. Cause of segregation is selective crystal solidification in the gradual change in composition of the solid phase. Melt began to appear after certain hypothermia during cooling, and the growth of germs in accordance with the general laws of crystallization. Each rigid layer has a different chemical composition. The first part of the solid phase ingredient is characterized with low concentration of the element, the last one, on the contrary, is characterized with very high concentration. Susceptibility to crystal alloy segregation is greater, when the temperature interval solidification of alloys and the horizontal distance between the liquidus and solidus lines are larger. Crystal segregation will also increase with increasing content of alloying elements, which occurs in these experimental alloys as containing 6—9% alloying elements. Crystal segregation can be removed by diffusion, for which it is necessary to create conditions by homogenization annealing. Гомогенізацію визначено як метод обробки, який полягає у витримці за високої температури поблизу ліквідуса (від 0,7 до 0,8 температури топлення) з метою усунення процесів дифузії, зумовлених хімічною неоднорідністю. Причиною сегрегації є вибіркове твердіння кристала за умов поступової зміни складу твердої фази. Розтоп починає з'являтися після деякого переохолодження під час остигання та росту зародків відповідно до загальних законів кристалізації. Кожний жорсткий шар має різний хімічний склад. Перша частина твердої фази мала низьку концентрацію легувальних елементів, остання - навпаки, високу. Сприйнятливість до сегрегації кристалічного стопу тим більша, чим більший температурний інтервал твердіння стопів та відстань по горизонталі між лініями ліквідуса і солідуса. Сегрегація кристала також зростає зі збільшенням кількості легувальних елементів, яка в даних експериментальних стопах становила 6 - 9 %. Сегрегація кристала може бути усунена дифузією, для цього необхідно створити умови шляхом гомогенізульвального відпалу сталі. Гомогенизация определяется как метод термообработки, который состоит в выдержке при высокой температуре вблизи ликвидуса (от 0,7 до 0,8 температуры плавления) с целью устранения процессов диффузии, связанных с химической неоднородностью. Причиной сегрегации является избирательное отвердевание кристалла при постепенном изменении состава твёрдой фазы. Расплав начинает появляться после некоторого переохлаждения во время остывания и роста зародышей в соответствии с общими законами кристаллизации. Каждый жёсткий слой имеет различный химический состав. Первая часть твёрдой фазы имела низкую концентрацию легирующих элементов, последняя – наоборот, высокую. Восприимчивость к сегрегации кристаллического сплава тем больше, чем больше температурный интервал отвердевания сплавов и расстояние по горизонтали между линиями ликвидуса и солидуса. Сегрегация кристалла также возрастает с увеличением содержания легирующих элементов, которое в этих экспериментальных сплавах составляло 6—9%. Сегрегация кристалла может быть устранена диффузией, для чего необходимо создать условия путём гомогенизирующего отжига стали.